High tolerance of two parasites in ornate tree lizards reduces the fitness costs of parasitism. (29th May 2020) - Paterson, J. E.; Blouin‐Demers, G.
Abstract: Parasites are ubiquitous and are presumed to have strong negative effects on host fitness. Despite this expectation, many parasites have negligible effects on their hosts in nature. Two hypotheses can explain why this might occur. Hosts can evolve resistance to parasites where their immune system attacks parasites (resistance hypothesis). The resistance hypothesis predicts that parasite load will decrease through time because of immune activity and that parasites have fitness costs to hosts. Alternatively, hosts can evolve tolerance to parasites and invest little energy in repelling attacks (tolerance hypothesis). The tolerance hypothesis predicts that parasites have no fitness costs to hosts. We tested these hypotheses with mark‐recapture data from six populations of a lizard host ( Urosaurus ornatus ) and two common parasites (ectoparasitic Trombiculid mites and haemoparasitic Plasmodium ). We found that parasite load was unrelated to lizard growth rates or survival. In addition, mite parasite load did not decrease through time. Thus, our data support the tolerance hypothesis. Ectoparasitic mites and haemoparasitic Plasmodium are therefore unlikely to be strong drivers of variation in Urosaurus ornatus population density at our study sites because of their negligible effects on host fitness. We encourage ecologists to measure carefully the effects of parasites on hosts, rather than assuming fitness costs of parasitism are present. Abstract : Parasites are ubiquitous and are presumed to have strong negative effects on host fitness. We found that parasite load of ornate tree lizards was unrelated to their growth rates or survival, and parasite load did not decrease through time. We encourage ecologists to measure carefully the effects of parasites on hosts, rather than assuming that fitness costs of parasitism are present.